Predictors of mortality in solid organ transplant recipients with bloodstream infections due to carbapenemase‐producing Enterobacterales: The impact of cytomegalovirus disease and lymphopenia. Issue 6 (6th February 2020) - Pérez‐Nadales, Elena; Gutiérrez‐Gutiérrez, Belén; Natera, Alejandra M.; Abdala, Edson; Reina Magalhães, Maira; Mularoni, Alessandra; Monaco, Francesco; Camera Pierrotti, Ligia; Pinheiro Freire, Maristela; Iyer, Ranganathan N.; Mehta Steinke, Seema; Grazia Calvi, Elisa; et al.
Abstract : Treatment of carbapenemase‐producing Enterobacterales bloodstream infections in solid organ transplant recipients is challenging. The objective of this study was to develop a specific score to predict mortality in solid organ transplant recipients with carbapenemase‐producing Enterobacterales bloodstream infections. A multinational, retrospective (2004‐2016) cohort study (INCREMENT‐SOT, ClinicalTrials.gov NCT02852902) was performed. The main outcome variable was 30‐day all‐cause mortality. The INCREMENT‐SOT‐CPE score was developed using logistic regression. The global cohort included 216 patients. The final logistic regression model included the following variables: INCREMENT‐CPE mortality score ≥8 (8 points), no source control (3 points), inappropriate empirical therapy (2 points), cytomegalovirus disease (7 points), lymphopenia (4 points), and the interaction between INCREMENT‐CPE score ≥8 and CMV disease (minus 7 points). This score showed an area under the receiver operating characteristic curve of 0.82 (95% confidence interval [CI] 0.76‐0.88) and classified patients into 3 strata: 0‐7 (low mortality), 8‐11 (high mortality), and 12‐17 (very‐high mortality). We performed a stratified analysis of the effect of monotherapy vs combination therapy among 165 patients who received appropriate therapy. Monotherapy was associated with higher mortality only in the very‐high (adjusted hazard ratio [HR] 2.82, 95% CI 1.13‐7.06, P  = .03) and high (HR 9.93, 95% CI 2.08‐47.40, P  = .004) mortality risk strata. A score‐based algorithm is provided for therapy guidance. Abstract : The authors develop a predictive risk score for a solid organ transplant recipient's for mortality in patients with bloodstream infections due to carbapenemase‐producing Enterobacterales, which is useful to differentiate patients who can be treated with antimicrobial monotherapy from those who should receive combination therapy.